Correction: A graphene hybrid supramolecular hydrogel with high stretchability, self-healable and photothermally responsive properties for wound healing. Issue 5 (18th January 2022) - Zhang, Haifeng; Zheng, Shiya; Chen, Canwen; Zhang, Dagan
Abstract : Correction for 'A graphene hybrid supramolecular hydrogel with high stretchability, self-healable and photothermally responsive properties for wound healing' by Haifeng Zhang et al., RSC Adv., 2021, 11, 6367–6373, DOI: ; 10.1039/d0ra09106e .